Emollients and moisturizers for eczema: abridged Cochrane systematic review including GRADE assessments. (1st November 2017) - van Zuuren, E.J.; Fedorowicz, Z.; Arents, B.W.M.
Summary: Eczema is a chronic inflammatory skin disorder with considerable impact on quality of life. Emollients or moisturizers are widely recommended, but are these effective and safe? We searched for randomized controlled trials (RCTs) in the Cochrane Skin Group Specialised Skin Register, CENTRAL in The Cochrane Library, MEDLINE, Embase, LILACS, the GREAT database and five trial registers to December 2015. We included 77 RCTs with 6603 participants. Seven studies (9%) were at low risk of bias, 34 (44%) had unclear risk and 36 (47%) were at high risk. The quality of the evidence was mainly low or moderate for the prespecified outcomes. The most important comparison, 'moisturizer vs. no moisturizer', showed improved Scoring Atopic Dermatitis values in the moisturizer group compared with no moisturizer [mean difference −2·42, 95% confidence interval (CI) −4·55 to −0·28], but did not meet the minimal important difference of 8·7. Fewer flares were seen (risk ratio 0·40, 95% CI 0·23–0·70) and the rate of flares was reduced (hazard ratio 3·74, 95% CI 1·86–7·50). The groups applying moisturizer used less topical corticosteroids over 6–8 weeks (mean difference −9·30 g, 95% CI 15·3 to −3·27). Glycyrrhetinic acid‐, urea‐ and glycerol‐containing creams worked better than their controls (vehicle, placebo or no moisturizer) according to both participants and physicians. More flares were reported with moisturizer alone than when combined with twice‐weekly fluticasone propionate (risk ratio 2·17, 95% CI 1·55–3·11). Adding moisturizers to topical anti‐inflammatory treatment was more effective than anti‐inflammatory treatment alone and resulted in fewer flares.